Effectiveness of hybrid learning model assisted by google classroom on writing negotiation text in class X RPL SMK Negeri 6 Konawe - Ana, Haerun; Udu, Sumiman; Saidiman, Saidiman (Educenter : Jurnal Ilmiah Pendidikan, 2025)
The increasing integration of technology in education highlights the need for effective learning models that enhance student engagement and learning outcomes. This study examines the effectiveness of implementing a hybrid learning model assisted by Google Classroom in improving students' learning motivation and negotiation text writing skills. Using a pre-experimental research approach with a one-group pretest-posttest design, the study involved 20 grade X students majoring in software engineering at SMK Negeri 6 Konawe. Data were collected through surveys and writing skills assessments. The findings indicate that hybrid learning with Google Classroom positively impacted students' motivation and writing proficiency, providing a more flexible and cost-effective learning experience. However, challenges such as limited internet access and reduced student interaction during online sessions were identified. The study contributes to the ongoing discussion on hybrid learning by demonstrating its potential benefits in language education while also highlighting areas for improvement. These findings suggest that schools and parents should provide additional support, particularly in enhancing internet accessibility, to maximize the effectiveness of hybrid learning.